2014
DOI: 10.1091/mbc.e13-01-0033
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic carboxypeptidase 5 regulates tubulin glutamylation and zebrafish cilia formation and function

Abstract: Zebrafish have four tubulin deglutamylases: Ccp1, Ccp2, Ccp5, and Ccp6. Except for ccp1, all deglutamylase genes are expressed during ciliogenesis in zebrafish. Only loss of ccp5 induces cilia hyperglutamylation and the complete spectrum of ciliopathy phenotype. ccp5 knockdown can bypass Fleer/Ift70 or Ift88 deficiency in zebrafish to form multicilia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 51 publications
1
52
0
Order By: Relevance
“…One study reported a smaller eye size in CCP5 zebrafish morphants, 14 and knock down of Ccp5 was found to increase cilia tubulin glutamylation which led to ciliopathy phenotypes and interferred multicilia motility. 13 In our study we were able to demonstrate the expression of RNA and protein in human retina. Moreover, AGBL5 expression was also found in mouse retina where it was located in the inner nerve fiber and inner ganglion cell layer (GCL), as well as in the inner (IPL) and outer (OPL) plexiform layers.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…One study reported a smaller eye size in CCP5 zebrafish morphants, 14 and knock down of Ccp5 was found to increase cilia tubulin glutamylation which led to ciliopathy phenotypes and interferred multicilia motility. 13 In our study we were able to demonstrate the expression of RNA and protein in human retina. Moreover, AGBL5 expression was also found in mouse retina where it was located in the inner nerve fiber and inner ganglion cell layer (GCL), as well as in the inner (IPL) and outer (OPL) plexiform layers.…”
Section: Discussionmentioning
confidence: 59%
“…In zebrafish, Ccp5 was found to be crucial for the embryonic development and ciliogenesis. 13,14 We therefore suggest that AGBL5 expression and thus deglutaminase function could be essential for developmental processes in the mouse and possibly in humans. The high RNA expression levels of Agbl5 in testis of P10 and P28 mice are in line with previously reported AGTBP1 expression where stronger antibody signals were detected in mouse testis from P18 onwards when compared to earlier stages.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Knockdown of ccp5 in zebrafish leads to a classic ciliopathy phenotype. 27 The biological plausibility of CDH16, encoding Ksp-Cadherin, is less clear, although other cadherins (PCDH15, CDH23, and CDH3) are known to cause RD. In the absence of an independent mutation in AGBL5 and CDH16, their candidacy remains to be proven.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mutation of the active site of the carboxypeptidase domain causes abnormal cilia development in zebrafish. 14 The protein-truncating variants, that is, p.(Trp592*) and p.(Ala502-Glyfs*15), are expected to result in complete loss of function due to premature translation termination and NMD.…”
Section: Agbl5 Is a Novel Gene Associated With Rpmentioning
confidence: 99%